Influence of grinding on machine parts with design notches - Holešovský, František; Novák, Martin (Manufacturing Technology Journal, 2009)
The final shape of machine parts is formed out by means of machining. At the machining the surface rises of definite properties, a given integrity, from these a surface usage comes out in the final machinery. This surface use is put especially its service life and loading capacity. The manufacturing watches the selected elements of the surface integrity for the functionality assurance of the machine parts. The machining influences in a different way the variant components. These are e.g. construction notches - the changeovers of single design components. The selection of a technology method of machining, the cutting tool at the finishing can affect notably both the function and service life of a machine part. The paper deals with the surface integrity at the surface load in machinery. There are the questions of the construction notches and next elements owing to the use of finishing method.
Keywords: grinding; loading; machine part; integrity; notch